The Influence of Financial Literacy, Social Media, and Self-Control on Fear of Missing Out (FoMO) Behavior in Generation Z Students - Christine Marina Wakarmamu; Yensawai E. Rumbiak (West Science Journal Economic and Entrepreneurship, 2026)
This study aims to analyze the influence of financial literacy, social media, and self-control on Fear of Missing Out (FoMO) behavior in Generation Z students. The study used a quantitative approach with an explanatory design. The research sample consisted of 77 respondents who were students of the Management Study Program, Faculty of Economics and Business, Cenderawasih University. Data were analyzed through validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple linear regression, partial tests, simultaneous tests, and coefficient of determination. The results showed that social media had a positive and significant effect on FoMO (B = 0.765; t = 4.283; Sig. = 0.000). Financial literacy did not have a significant effect on FoMO (B = 0.037; t = 0.119; Sig. = 0.906), while self-control had a negative but insignificant relationship (B = -0.277; t = -1.416; Sig. = 0.161). Simultaneously, financial literacy, social media, and self-control significantly influence FoMO (F = 7.426; Sig. = 0.000) with an R Square value of 0.234. These results indicate that 23.4% of FoMO variation can be explained by the three independent variables, while the rest is influenced by other factors outside the model. This study confirms that social media is the main determinant in the formation of FoMO in Generation Z students, while financial literacy and self-control have not shown a significant partial influence.